A primary melanoma and its asynchronous metastasis highlight the role of BRAF, CDKN2A, and TERT. (11th December 2014) - Hosler, Gregory A.; Davoli, Teresa; Mender, Ilgen; Litzner, Brandon; Choi, Jaehyuk; Kapur, Payal; Shay, Jerry W.; Wang, Richard C.
Abstract Background Alterations in pathways including BRAF, CDKN2A, and TERT contribute to the development of melanoma, but the sequence in which the genetic alterations occur and their prognostic significance remains unclear. To clarify the role of these pathways, we analyzed a primary melanoma and its metastasis. Methods Immunohistochemistry for BRAF‐V600E, Sanger sequencing of BRAF and the TERT promoter, fluorescence in‐situ hybridization, and telomere analyses were performed on a primary melanoma and its asynchronous cerebellar metastasis. Using the log‐rank test and Cox‐proportional model, the cancer genome atlas (TCGA) cohort of melanomas was analyzed for the effect of BRAF mutation and CDKN2A loss on survival. Results The primary melanoma expressed mutant BRAF‐V600E and possessed a homozygous deletion of CDKN2A. In addition to these early defects, the metastatic lesion also possessed evidence of aneuploidy and an activating mutation of the TERT promoter. In the TCGA melanoma cohort, there was a non‐significant trend toward poor prognosis in early stage cutaneous melanoma patients with concomitant BRAF mutation and CDKN2A loss. Conclusion BRAF mutation and CDKN2A loss occurred early and TERT promoter mutation later in a case of lethal metastatic melanoma. The effects of these pathways on survival warrant further investigation in early stage cutaneous melanoma patients.